2008
DOI: 10.2165/0126839-200809060-00007
|View full text |Cite
|
Sign up to set email alerts
|

Dosage Form Proportionality and Food Effect of the Final Tablet Formulation of Eslicarbazepine Acetate

Abstract: The bioequivalence criteria between the ESL 400 mg and 800 mg tablets were met and dosage form proportionality was demonstrated. The presence of food had no influence on ESL pharmacokinetics, indicating that ESL can be administered without regard to meals with no significant effects on drug disposition or extent of systemic exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In contrast, ESL is a prodrug that is converted only to S-MHD, which is also known as S-licarbazepine or ESL. 113 , 114 The pharmacokinetics of ESL are not affected by factors such as food consumption, 115 , 116 age, 117 or gender. 118 Our results showed ESL 1200 mg/d was ranked seventh in terms of seizure response.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, ESL is a prodrug that is converted only to S-MHD, which is also known as S-licarbazepine or ESL. 113 , 114 The pharmacokinetics of ESL are not affected by factors such as food consumption, 115 , 116 age, 117 or gender. 118 Our results showed ESL 1200 mg/d was ranked seventh in terms of seizure response.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma levels of parent drug (ESL) are usually undetectable. In the present study an achiral method was used, thus not allowing to distinguish between eslicarbazepine and its minor metabolite, ( R )-licarbazepine; in such cases, the mixture is reported as BIA 2-005 [19, 20]. …”
Section: Methodsmentioning
confidence: 99%
“…Prior to shipment to the laboratory for the analytical assays (Swiss Bioanalytics AG, Birsfelden, Switzerland), the resulting plasma was separated into aliquots of 0.75 mL and stored at −20 °C. The lowest level of quantification (LLOQ) was at 10 ng/mL [19, 20]. …”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the authors concluded that dose adjustments of ESL based on gender will not be required 39. Finally, studies concerning possible influences of warfarin (at a subtherapeutic level)40 or food41 on ESL pharmacokinetics in healthy volunteers revealed no influence of either on ESL pharmacokinetics, but did show a small and statistically significant reduction in systemic exposure to S-warfarin, with no effect on R-warfarin, on the International Normalized Ratio 40,41…”
Section: Drug Interactionsmentioning
confidence: 99%